2022
DOI: 10.1186/s12913-022-08261-2
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of working as early career allied health professionals and doctors in rural and remote environments: a qualitative systematic review

Abstract: Background Maintaining a health professional workforce in rural and remote areas poses a significant challenge internationally. A range of recruitment and retention strategies have had varying success and these are  generally developed from the collective experience of all health professions, rather than targeted to professional groups with differing educational and support contexts. This review explores, compares and synthesises the evidence examining the experience of early career rural and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 65 publications
(178 reference statements)
0
20
0
Order By: Relevance
“…More needs to be done to promote positive aspects of rural practice 38 and further investigation is needed, with longitudinal follow‐up of graduates as they mature professionally. Roberts et al 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More needs to be done to promote positive aspects of rural practice 38 and further investigation is needed, with longitudinal follow‐up of graduates as they mature professionally. Roberts et al 9 .…”
Section: Discussionmentioning
confidence: 99%
“…More needs to be done to promote positive aspects of rural practice 38 and further investigation is needed, with longitudinal follow-up of graduates as they mature professionally. Roberts et al 9 suggested that fostering professional identity can bring social and structural elements together.…”
Section: Factors That Influenced the Decision Regarding Practice Loca...mentioning
confidence: 99%
“…[41] An international study investigating rural and remote practices across ve countries found that practising in rural and remote areas posed a signi cant challenge to SOP due to barriers such as excessive travel and a disproportionate workload. [42] This viewpoint was based on the knowledge that rural practitioners encountered challenges due to travel distances and excessive workloads. [42] Evidence: research-derived and practice-based…”
Section: Geographical Locationmentioning
confidence: 99%
“…Previous studies have explored strategies to address workforce challenges in rural and remote areas, but these predominantly address doctors' needs (5,6). Medical and allied health professionals face different challenges and opportunities in relation to training, career advancement, supervision, organisational support and personal circumstances and different workforce strategies are required accordingly (7).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently there were limited opportunities for allied health to be recognised for advanced skills in rural and remote practice (9), along with career advancement opportunities and adequate retention strategies (10). There is increasing recognition that structured training and professional support assists rural and remote allied health professionals to develop and maintain skills that advance their careers (7,9,11). In the Australian context, the state of Queensland's Health service paved the way for postgraduate training and workforce development initiatives by introducing allied health rural generalist training positions from 2013 to develop and recognise the specialist skills and knowledge required for rural and remote practice (12) and to improve workforce outcomes.…”
Section: Introductionmentioning
confidence: 99%